Improving first‐time donor attendance rates through the use of enhanced donor preparation materials. Issue 6 (2nd February 2016) - Masser, Barbara; France, Christopher R.; Foot, Jayne; Rozsa, Amy; Hayman, Jane; Waller, Daniel; Hunder, Everard
Abstract : BACKGROUND: Many nondonors are positive about blood donation and this motivates booking an appointment to donate. However, as their appointment approaches barriers to donating—such as anxiety—may become salient and deter attendance. Building on research of France and colleagues demonstrating the positive effect of enhanced preparation materials on donor recruitment, this study sought to determine whether these materials could effectively boost first donation appointment attendance. STUDY DESIGN AND METHODS: A field study comprising a 3 (brochure: none, e‐mail, hard copy) × 2 (national call center [NCC] contact: none, call) between‐subjects design was conducted with 3646 nondonors who had scheduled their first appointment. Participants in the brochure conditions received either a hard copy or an e‐mailed link to electronic materials modeled on the donor preparation research of France and colleagues. Participants in the NCC call condition also received a call scripted in line with these preparation materials. The key outcome was new donor attendance rate. RESULTS: Although first‐appointment attendance rates were high in the control (no additional contact) condition at 85.07% of those not canceling in advance, dual exposure to the preparation materials through a NCC call and an electronic brochure boosted attendance. The relative risk of attending in the NCC call and electronic brochure condition was 1.0836 (95% confidence interval, 1.0352‐1.1343; p = 0.0006), with attendance 8.36% higher than in the control. This gain in attendance came at a relative increase in recruitment costs of 2%. CONCLUSION: The use of tailored communication to address new donors' concerns and prepare them for donating bolsters attendance rates.